Correlation of Coronary Angiography Findings with Cardiovascular Risk Factors in a Tertiary Center in Nepal - Bhattarai, Nishan; Koju, Rajendra; Humagain, Sanjaya; Pathak, Surya Raj; Silwal, Srijan; Pote, Sneha; Sapkota, Kritendra; Pathak, Sujan (Journal of Nepalgunj Medical College, 2025)
Introduction: Coronary artery disease is one of the most common heart problems and a major cause of illness and death around the world. It occurs when the coronary arteries become narrower due to atherosclerosis. Risk factors contributing to atherosclerosis include high blood pressure, diabetes, smoking, high cholesterol, being overweight, and physical inactivity. Coronary angiography is a highly effective method for diagnosing coronary disease. Having more than one cardiovascular risk factor at the same time has been linked to more serious and widespread forms of coronary artery disease. Aims: To correlate coronary angiographic findings of coronary artery disease with cardiovascular disease risk factors. Methods: A hospital-based cross-sectional descriptive study was conducted among 170 patients who had undergone coronary angiograms in a Semi-urban tertiary care center. Participants were enrolled prospectively after taking ethical approval from the Institutional Review Committee, Kathmandu University School of Medical Sciences. Various risk factors and coronary angiogram findings were noted. Data were collected in Microsoft Excel and analyzed in SPSS version 21. Results: The mean age of the patients in the study was 60.81±10.70 years, and 35.88% of them were female. The most prevalent risk factor for coronary artery disease was hypertension (73.53%), and the most common symptom was chest pain, seen in 83.50% of cases. ECG changes were seen in 87.65%, and 69.41% of cases had coronary artery disease findings on coronary angiogram. The most common coronary angiogram finding was single-vessel disease, seen in 28.24% of cases. Significant CAD findings correlated well with hypertension, diabetes, smoking, and dyslipidemia, but no correlation was found with obesity and family history of CAD. The risk of having multivessel disease was higher among those who had multiple risk factors. Conclusion: This study highlights hypertension as a key modifiable risk factor for CAD. The risk of significant CAD increases in the presence of modifiable cardiovascular risk factors, and the risk of having multivessel disease, i.e., diffuse disease or significant disease burden, is high in the presence of multiple risk factors as compared to single risk factors.